PEMBELAJARAN DI ERA PANDEMI COVID’19 DALAM PENDEKATAN KONTEKSTUAL - Abdul Manaf (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
Humans in life need to meet two needs, physical needs are needed by the body in order to be able to utilize all the muscles in the human body and utilize the brain in life and spiritual needs are abstract needs in the form of mind and reason, fulfillment of the mind and will be done through education. Therefore, whatever obstacles and constraints those needs must be met with various methods, strategies, methods and approaches that must be done, if only one of them is fulfilled in an abnormal human life, then for balance in life it is necessary to fulfill both needs at the same time.